The Effectiveness of The Rose (Reconnection of Science and English) Module in The Achievement of Science and English Competencies - Ronnel Joseph Competente; Joyce De Guzman (SEAMEO QITEP in Science, 2022)
DepEd's Basic Education – Learning Continuity Plan (BE-LCP) as described in DO. No. 12, s. 2020 called for measures that will bring education equitably to all its learners. The researchers saw the merging of Science and English into one learning material using a content-based instruction approach as an apt response to this call. Therefore, the ROSE (Reconnection of Science and English) Module was crafted. This experimental mixed-methods design action research sought to (1) determine the perceptions of the Grade 10 students on the ROSE (Reconnection of Science and English) Module in terms of (a) content, (b) activities, (c) the merged/integrated module as a whole; (2) determine if there was a significant difference between the students' pre and post-test results using the ROSE Module; and (3) identify how had the ROSE Module helped students achieved DepEd's Most Essential Learning Competencies (MELCs) in Science and English subjects. A survey questionnaire was used to find answers to objectives 1 and 3, while a diagnostic test was utilised as the instrument for objective 2. After two quarters of using the ROSE module, data on the pre and post-test results during the first and second quarters revealed a significant difference in the Grade 10 students' scores. Survey responses also showed that the respondents agreed to the Module's (a) content, (b) activities, and (c) merging/integration. Finally, despite the difficulties, confusion, and many other challenges, most of the respondents agreed that the ROSE module taught them academic skills such as writing and thinking as well as life skills such as responsibility, time consciousness, patience, perseverance, industry, and self-reliance.